Upaya Pencegahan dan Pengendalian Penyakit Jantung Koroner Berbasis Rumah Sakit: Literatur Review - Azzahra', Lama'ah (STIKES ADVAITA MEDIKA TABANAN, 2024)
Background: Deaths from Coronary Heart Disease are still a major problem in the world, including in Indonesia. CHD is also a health problem that can have a socio-economic impact. Purpose: This study aimed to determine how prevention and control efforts can be made for people with hospital-based Coronary Heart Disease. Methods: This type of research was a literature review of several articles that have been comprehensively collected through Google Scholar, Springerlink, ScienceDirect by using keywords in the literature search was